This action might not be possible to undo. Are you sure you want to continue?

PDEs. The ﬁrst one is the method of characteristics, which is particularly useful when solving ﬁrst order equations. 1 . C lassiﬁcation of ﬁrst-order equations. The general form of ﬁrst-order PDE ( in R2 ) : F( x , y , u , ux , u y) = 0 , or in R3 : ( x , y ) ∈ D ⊂ R2 . (1) ( 2) ( 3) ( 4)

F( x , y , z , u , ux , u y , uz ) = 0 . Often the following notation is used in 2D: p = ux , q = u y thus the equation can be written as F ( x , y , u , p, q ) = 0 . The linear equations can be classiﬁced into the following cases, from easier to more diﬃcult: 1 . Linear: 2. Semi-linear: 3. Quasi-linear: 4. General case. F ( x , y , u , u x , u y ) = a ( x , y ) u x + b ( x , y ) u y + c( x , y ) u − d( x , y ) . F ( x , y , u , u x , u y ) = a ( x , y ) u x + b ( x , y ) u y − c( x , y , u ) . F ( x , y , u , u x , u y ) = a ( x , y , u ) u x + b ( x , y , u ) u y − c( x , y , u ) .

( 5) ( 6) ( 7)

2. Method of characteristics. We try to ﬁnd a method to solve the general ﬁrst-order quasi-linear equation a ( x , y , u ) u x + b ( x , y , u ) u y = c( x , y , u ) . ( 8)

Let’ s start by thinking geometrically. Consider the 3 dimensional space with coordinates ( x , y , u ) . Assume that u = u ( x , y ) is a solution to the equation, it is clear that it represents a surface in the ( x , y, u ) space. Now we explore the geometrical meaning of the equation. Observe that the equation can be written in the form of an inner product a( x , y , u) a( x , y , u) ux ux b ( x , y , u ) ⊥ u y . b( x , y , u) · u y = 0 ( 9) c( x , y , u ) −1 c( x , y , u ) −1

**Therefore all we need to do is to understand the relation between the vector First introduce a new function Ψ : R
**

3

¡

R through

ux uy − 1

and the solution. ( 1 0)

Φ ( x , y , u) = u − u( x , y) .

Note that in the RHS of the above, the ﬁrst u is a variable, the second u is a function. For example, suppose u ( x , y ) = x 2 + y 2 , then the corresponding Φ ( x , y, u ) = u − x 2 + y 2 . Now we easily see that Φx ux uy = − Φ y = − ∇Φ . (11) Φu −1

Y . The curves mentioned above are called the families of characteristic curves of the equation. u) ux uy − 1 which that the vector curve a of b . y . b are constant . Conversely. As a consequence is perpendicular to the solution surface u = u ( x . ψ) = 0 . we will show how to apply this method. The above understanding leads to the following “method of characteristics” due to Lagrange. 8. u ) .order. u) c( x . y. Equations with constant coeﬃcients. from the equation we know that a b c is perpendicular to the vector must be tangent to the surface u = u ( x . y .Recall ux uy − 1 means that geometrically. ( 1 9) . As a consequence. quasi. Remark 4. 3. y . The characteristic equations are dx d y du = = . ∇ Φ ( and also − ∇ Φ ) is a normal vector of the surface Φ = 0 . ψ are obtained through solving the characteristic equations. and any intersection of the level sets of φ and ψ is a solution of the characteristic equations dx d y du = = . u ) satisﬁes F( φ . the main technique in getting φ and ψ is a c = b d a±c a c = = . b . U ) ( 1 3) ds dU = c( X . And each F gives a solution to the original equation. y . c and d are just constants. We start with the simplest case. We start from the simplest case. y . b±d b d ( 1 8) In the following.linear PDE a ( x . a ( x . u) b( x . y . Theorem 1 . Solving linear ﬁrst-order equations. U ) ( 1 4) ds must be contained in one of the solution surfaces. any integral satisfying dX = a( X . Solution. U ) ( 1 2) ds dY = b( X . Y . y ) . a b c On the other hand. As we will see soon. Y . Example 5. We have shown that the equation is equivalent to the geometrical requirement that is any X( s) Y( s) U( s) is tangent to the solution surface u = u ( x . 3( b) ) Find the general solution of the equation a u x + b u y = 0. φ . The general solution of a ﬁrst. u ) and ψ ( x . u ) u y = c( x . any surface “woven” by such integral curves is a solution surface. 3. a b c ( 1 7) ( 1 5) Remark 2. y ) . As we will see. c Now we summarize. y ) . ( 1 6) where F is an arb itrary function of φ ( x . Remark 3. where a . b 0 a ( 20) a . y . ( § 2. 1 . u ) u x + b ( x .

we obtain f ( 2 x ) = sin x ( 26) Therefore x f ( x ) = sin . one may be tempted to conclude d u − C e− a −1 − 1 cx =0 ( 34) and try to use u − C e − a c x as ψ . the value of the solution along some speciﬁc curve in the plane is prescribed. This is obviously wrong as d somehow disappeared. § 2. 5( a) ) Oftentimes. 8. notice that thus we can take d( a y − b x ) = a d y − b d x = 0 . ( 21 ) ( 22) ( 23) ( 24) As a consequence. ψ = a y − b x. 2 2x−3y . a b −1 −1 dx du du = = a− 1 d − a− 1 c u u = C e − a c x + c− 1 d d e a c x u − c− 1 d = 0 a d− cu dx down ( 28) ( 29) ( 30) φ = b x − a y. In the above. Obviously we can take φ = u . 0) = sin x. From the above example we know that the general solution takes the form u = f ( 2 x − 3 y) . Example 9. ( c. y ) = sin As a consequence and gives Example 7. Now substituting this into the initial condition. y . ψ) = 0 u = c− 1 d + e − a − 1 cx f ( b x − a y) . ψ = ea − 1 cx u − c− 1 d ( 31 ) ( 32) ( 33) F( φ . y . a b d− cu We have dx d y = d( b x − a y ) = 0 . d are not 0 ? The method still works. ( 25) Solution. This means for an arbitrary function f . Remark 8. d 0 ) What happens when the c.What we need are two functions φ ( x . d ψ = 0 along the characteristics. u ) and ψ ( x . 2 ( 27) u ( x . Some times people use the following “method of characteristics”: . solve 3 ux + 2 u y = 0. Example 6. It is their values that are arbitrary constants. the solution satisﬁes for any function F . One should keep in mind that neither φ or ψ can involve arbitrary constants. F( a y − b x . u ( x . u ) such that d φ = 0 . For example. We write the characteristic equations dx d y du = = . ( C auchy problem. u) = 0 u = f ( a y − b x) . For ψ .

t ) . then you have φ and ψ .First solve then solve dx = a. ( 47) Solution. Anyone who does not believe this should try using this method to the following examples with non-constant coeﬃcients. We need to ﬁrst ﬁnd the general solution. Pick any two of them. ( § 2. Example 1 2. Example 1 1 . ( § 2. 8. This is equivalent to our method but considerably more complicated to use. − Find the general solution The characteristic equations are Using dx d y du = = . Finally represent s . Equations with non-constant coeﬃcients. ( 40) ( 41 ) ( 42) ( 43) ( 44) ( 45) ( 46) d y du = 1 y d( u − log y ) = 0 . how to ﬁnd out φ and ψ eﬃciently? Unfortunately there may not be any short-cut. −x y 1 dy dx = y −x y dx + x d y = 0 ( 38) ( 39) d( x y ) = 0 . Remark 1 0. 8. t by x . The characteristic equations are Using we obtain Thus φ = x y. then using the value on y = x 2 to determine the arbitrary function involved. The characteristic equations consists of three equations. from we obtain d u = d log y y u y − x ux = 1 . 3( h) ) Find the general solution of Solution. 2. As a consequence we can take Putting these together we obtain which gives ψ = u − log y. ( 37) dx d y du = = . with u = 2 on y = x 2 . F ( x y . y and obtain the solution. If you can ﬁnd general solutions. One may wonder. But this fails when any coeﬃcient involves all other variables. 3. x y 2xy dx d y = y x ( 48) ( 49) . One way to systematically ﬁnd φ and ψ is the following. 5( c) ) Find the solution of the following Cauchy problem: x ux + y u y = 2 x y . ds dy =b ds ( 35) ( 36) us + c u = d to obtain the solution u in the form u = u ( s . u − log y ) = 0 u = log y + f ( x y ) . On the other hand.

y x 3 ( 55) ( 56) u( x . The characteristic equations are ( 58) ( 59) ( 60) From we have On the other hand. ( § 2. . x ( 53) d u = 2 x d y = 2 y d x = x d y + y d x = d( x y ) ψ = u − x y. we have therefore The general solution satisﬁes F − y =0 x can take φ = y . x d( u − x y ) = 0 ( 50) ( 51 ) ( 52) y . The characteritic equations are dx d y du = = x y u+1 ( 66) with u ( x . we have x3 + f ( x) = 2 ( 54) As a consequence f ( x) = 2 − x3. d( u − y ) u− y =− y dy du u =− +2 dy y d( ( u − y ) y ) = 0 . Using the formula for the general solution.we obtain d On the other hand. dy du dx = = . F x2 + y2 . y) = x y + 2 − 4. that is u x . ( 62) ( 63) ( 64) Example 1 4. we have dy du = − x y x ( u − 2 y) φ = x2 + y2 . 5( g) ) Solve x ux + y u y = u + 1 Solution. ( § 2. y ) = x 2 on y = x 2 . x2 = 2. u− xy =0 x u=xy+ f Determine the solution. Example 1 3. 8. y . We have u = 2 along y = x 2 . y ( u − y) = 0 u = y + y− 1 f x2 + y2 . 3( g) ) Find the general solution of the following equation: y2 ux − x y u y = x ( u − 2 y) . 8. Solving semi-linear ﬁrst-order equations. − x y x ( u − 2 y) y2 dy dx = y2 − xy d x2 + y2 = 0 ( 57) Solution. ( 65) . ( 61 ) Thus we take Now gives ψ = y ( u − y) .

x ψ= u+1 . ( 78) Thus the formula may not be unique. y x− y y+u d( y + u ) dx = y+u x ( 72) Solution. 5( h) ) solve u ux − u u y = u2 + ( x + y) 2 with u = 1 on y = 0 . x ( 67) ( 68) ( 69) ( 70) x2 − 1. ( 76) As a consequence. − u u2 + ( x + y) 2 u dx dy = u −u ( 80) ( 81 ) ( 82) d( x + y ) = 0 φ = x + y. Example 1 7. dy du dx = = . dy du = − u u2 + φ2 ψ = e2 y u2 + φ2 . ( § 2. x2 = x2 f ( x) = x + x − 1 . u2 − ( x − y) 2 = 0 . ( 79) Solution. 8. ( § 2. 8. y ( 71 ) u=xf y − 1. The characteristic equation are We have Then we have dy du dx = = .which easily lead to φ= Thus Now the Cauchy data implies thus As a consequence u( x . The characteristic equations are ( 73) ( 74) ( 75) From this we have Thus we can take On the other hand. Solving quasi-linear ﬁrst-order equations. x x f ( x) − 1 = u x . Example 1 5. 3( f) ) Find the general solution of ( y + u ) u x + y u y = x − y. we have d x2 − ( y + u) 2 = 0 . y y +x x x −1 − 1 = y+ 5. Note that. Remark 1 6. y) = x y . . the solution is given by F x 2 − ( y + u) 2 . in the above we can also use d y d( x + u ) = x+u y ( 77) d x+u y = const . d( x − y ) du = x− y u d u2 − ( x − y) 2 = 0. φ = x2 + ( y + u) 2 .

Equations with more than two variables. 1 + φ2 ≡ 0. The method of characteristics can be applied to higher dimensional problems with no diﬃculty in principle – it indeed becomes more diﬃcult in practice! Example 1 8. 1 ( 93) =0 ( 92) dy dz = − z yφ d z 2 + y2 φ = 0 η = z 2 + y 2 φ. The characteristic equations are ( 88) ( 89) The last invariant can be obtained through dy dz = − xz xyφ dx dy = y −x d x2 + y2 = 0 ψ = x2 + y2 . let’ s denote them by φ . we observe dx dy = yz − xz ( 87) Solution. ψ ) = ψ − φ2 + 1 e2 y u2 + ( x + y) 2 − 1 + ( x + y) 2 = 0 u= ± 1 + ( x + y) 2 ( 83) ( 84) ( 85) . ψ and η . For the second invariant. Clearly one can take φ = u. z 2 + y2 x2 + y2 for arbitrary f. z 2 + y2 x2 + y2 which gives u = f x 2 + y2 . ( 86) e − 2 y − ( x + y) 2 1 /2 6. ( 90) Therefore the solutions are obtained by setting F u . ( 91 ) 1 . 8. . dy dz du dx = = = . x2 + y2 . F( φ . ( § 2.Now from the Cauchy data we have Therefore eﬀectively F has to be and the solution satisﬁes which leads to F φ . K eep in mind that this f will be determined once some C auchy data is given. 0 y z − x z x y ( x2 + y2 ) This time we need three invariants. 8( d) ) Solve the following equation y z ux − x z u y + x y x2 + y2 uz = 0 .

Description of the method of characteristic for solving differential equations.

Description of the method of characteristic for solving differential equations.

- Elementary Course on PDEs by TMK
- Class 2
- Solve Wave
- FET_Gorkov
- R. Radha, S. Vijayalakshmi and M. Lakshmanan- Explode-Decay Dromions in the Non-Isospectral Davey-Stewartson I (DSI) Equation
- ADOMIAN Decomposition Method for Solvin1
- An Improved HMF with PDE for Cellular Imaging
- Charact
- nptel cfd notes
- General Solutions and Fundamental Solutions of Varied Orders to the Vibrational Thin, The Berger, And the Winkler Plates
- Asian Geometric
- Design Sensitivity Analysis
- Parabolic Pde
- cfd
- PDE 2011 Impa
- Forsyth Draft 1
- Polifke Iit m
- diffeqdim
- mock test -2 math
- 16-radiosity
- A 0260104
- Spm Questions
- Black Hole Control 1
- Additional Mathematics - Chapter 2
- 1009.3176v1
- DiffEq
- Axisymmetric Flow of Navier-stokes Fluid
- Smiths Prize Exam Stokes
- Diffusion
- Finned Surface
- Method Characteristic

Are you sure?

This action might not be possible to undo. Are you sure you want to continue?

We've moved you to where you read on your other device.

Get the full title to continue

Get the full title to continue reading from where you left off, or restart the preview.

scribd